Analisis Kompetensi Kerja Tukang Plester di Kota Palu - Asnudin, A.; Ridwan, M.A. (Civil Engineering Department, Tadulako University, 2021)
One effort to empower the implementation of construction projects in order to maintain the quality of the final work is the application of competency standards for workers who hold a strategic position in determining the quality of the final building, in this case plaster workers. The aims of this research was to know the application of plasterer competency standards based on the Indonesian National Work Competency Standards (SKKNI) on building projects in Palu City. This research was conducted on plasterers of buildings in the city of Palu. The research method used was literature study, the primary data collection was done by distributing the questionnaires. The selected respondents were plasterers. Data were processed by using descriptive statistical methods and using the Relative Rank Index (RRI). The results showed that the application of plasterers' work competency standards based on SKKNI was around 80% to 90% which had been well implemented, namely, carrying out Preparation of Plastering Work, Carrying Out Plaster Mixing Mixes, Carrying Plaster Work. In addition, around 20% to 30% have not been well implemented, namely, the use of PPE and WSE, Making Job Reports.